Engineering a Dialogue with Klara, or Ethical Invention with Generative AI in the Writing Classroom - Kotzeva, Elitza; Anders, Brent (Journal of Academic Writing, 2023)
In this teaching practice article, we discuss the possibilities of integrating AI into the writing classroom utilizing prompt engineering techniques. We propose a strategy for prompt engineering in which we see AI as an audience and interlocutor during the invention process. We consider using the method in preparation for argument composition and with that we propose an ethical model for teaching writing based on a view of rhetoric as both technê and praxis. To draw attention to the ethical question in relation to human—non-human interactions, we use as metaphor for AI tools the image of Klara, an android who serves as a children’s companion in Ishiguro’s novel Klara and the Sun (2021).